Nutraceutical Approaches to Cardiovascular and Metabolic Diseases: Evidence and Opportunities (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
A major task for health professionals and health systems is effectively preventing and treating cardiovascular and metabolic diseases. This reprint offers an updated set of experimental and clinical information on the usefulness of nutraceutical products for the management of cardiometabolic diseases, which range from obesity and diabetes mellitus and their complications to hypercholesterolemia. The nutraceutical option may be used according the “beyond diet, before drug” strategy and is particularly relevant in the cardiometabolic field. The chapters of this reprint offer a deep insight into relevant issues in this nutraceutical field, such as experimental research for the preclinical identification of interesting compounds of natural origin, quality of nutraceutical products and their efficacy and safety, regulatory aspects, and the quality of evidence-based medicine.